Improving the growth indices and carcasses quality of Acipenser persicus fingerling using Bacillus licheniformis, Bacillus subtilis, and Saccharomyces cerevisiae - F. Darafsh; M. Soltani; H.A. Abdolhay; M. Shamsaei Mehrejan (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2019)
To determine the effect of D-Pro probiotics (Bacillus licheniformis, Bacillus subtilis) and Saccharomyces cerevisiae in Persian sturgeon’s diet on the growth indices and biochemical analysis of the carcass, a total of 2400 Persian sturgeon species were randomly selected, with a mean weight of 4.00±0.10 g (mean ± standard error) and a mean length of 9.91±0.35 cm (mean ± standard error), and were assigned to four treatment groups, each of which was carried out with three replications. The present study was conducted within 60 days in Dr. Beheshti Center of Proliferation and Restoration of Persian Sturgeon (Guilan province). The treatments were 1) 5 g/1 kg of D-Pro, 2) 5g/1kg of Saccharomyces cerevisiae, 3) a mixture of 5 g/1kg of D-Pro and 5 g/1kg of Saccharomyces cerevisiae, and 4) a control group )a basic diet without any probiotics and yeasts(. Results of the analyses showed that the highest mean weight was obtained in the D-Pro treatment. The D-Pro treatment had the highest increase in length and the lowest feed conversion ratio which were significantly different compared to other treatments (P<0.05). Using D-Pro in their diet led to a carcass fat increase and this increase was statistically significant (P<0.05). By adding D-Pro to their diet, the carcass moisture decreased and this decrease resulted in a significant difference in the carcass moisture content compared to the control group (P<0.05). The levels of whole carcass ash were not significantly different in the D-Pro and Saccharomyces cerevisiae treatments compared to the control group (P>0.05). However, differences in the levels of whole carcass ash were observed between the D-Pro and Saccharomyces cerevisiae treatments, such that the levels of ash significantly increased compared to the D-Pro treatment (P<0.05). The oral consumption of 5g of D-Pro probiotic in the Persian sturgeon’s diet increased growth and growth indices and is recommended to be used in the aquaculture industry.